Leader-member exchange affects work engagement: The role of psychological well-being mediation - Permatasari, Winny Yus; Suhariadi, Fendy (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2019)
Work engagement has a contribution to the success of an organization. Governmental institutions are often criticized for showing less satisfying performance and less effective services due to the misconducts of the civil servants such as coming late to work, leaving at working hours, and being less enthusiastic at work. This study aimed to examine civil servants' working conditions using three variables, namely leader-member exchange, psychological well-being, and work engagement. The measuring tools used referred to the Leader-Member Exchange Multidimensional (Liden & Maslyn, 1998), Psychological Well-being Scale (Ryff, 1989) and Utrecht Work Engagement Scale (Schaufeli & Bakker, 2004). There were 80 civil servants involved in this study as the subjects. They were selected using simple random sampling technique. Statistical techniques used in this study Structural Equation Modeling-Partial Least Square (SEM-PLS) with Warp PLS 5.0 Software. The result indicated that the three variables had a positive correlation with one another, and psychological well-being mediated the influence of leader-member exchange on work engagement.